PENGGUNAAN BAHAN AJAR DALAM PEMBELAJARAN TEMATIK SUBTEMA KETERATURAN YANG MENAKJUBKAN KELAS VI - Karunia Mukti Sari; Ulpah Maspupah (CV. Amerta Media, 2022)
Teaching materials are an important part that can affect the process of running a learning. A teacher requires materials or materials that are systematically arranged based on the competencies that students must master so that learning becomes directed at the learning objectivites to be achieved. At this time the curriculum being implemented is Curriculum 13 with a thematic learning approach. Thematic learning is learning that integrates several subjects into one discussion theme. With this integration, it causes difficulties for students in gaining understanding because the material is incomplete so that use of supporting teaching materials is needed to support the learning process. The implementation of this study aims to determine the types of teaching materials used and the use of these types of teaching materials in the thematic learning of the sub-theme of Amazing Order in Class VI. The type od research used in this research is field research which is descriptive qualitative. From the research that has beeb done, the results of the research show that the use of teaching materials in the thematic learning of the sub-theme of Amazing Order in Class VI use thematic books, worksheets, pictures, models, videos, audio, and interactive teaching materials in the form of power point slides. And in its use adjusted to the materials. Thematic books are the main teaching materials, worksheets are for evaluation, while pictures, models, videos, audio and power point slides are used in certain materials only.Keywords: teaching materials, thematic learning